Martin R. Howard. The fevered flight; a medical history of the American revolution, 1775-1783. Naval Inst Pr, 2023, 276 pp. ISBN-13: 978-1399084826. - Olalowo, Olawumi Helen (Cuadernos de Historia, 2024)
In tracing the trajectory of medical treatment during the American revolutionary war and discussing the specifics of each war front, Howard interrogated the several health challenges that plagued the war camps, describing adequately the treatment and surgical methods adopted by the American and British medical departments during the war and the impact of diseases on the native Americans and the black populace, including the unwavering efforts to curb the spread of smallpox and digging out the strategies adopted to curb Covid-19. This most recent pandemic has posed a great challenge to America and the global health system. Thus, this, coupled with the several unique graphical representations of the battlefield activities, a skillful pattern of chapter introduction with a monograph or line of thought creates in the readers the desire to take their minds on a voyage of feasting on every page of this book.